Mozart 2.0 - Tarsik, Nor Famiza; Selamat, Nordibradini; Hassim, Hasniza; M. Said, Salasiah (Universiti Teknologi MARA, Kedah, 2018)
Autism Spectrum Disorder (ASD) is a developmental disability that affects how children understand the world. The intellectual ability of children with an ASD can range from severe learning difficulties with little communication, have difficulties with their imaginary skills and an ability to think in a flexible way. They will often like routine and structure in their life and find change difficult. Every child has the right to a free appropriate education. Therefore, this project is initiated for children with autism (speech delay) with librarians, library media teacher and special education teacher cooperation. Most libraries incorporate elements of several established approaches. It is important for libraries to evaluate prospective interventions for a student on an individualized basis, as well as keep in mind the need to use evidence-based methods and strategies. Therefore, this project named as Mozart 2.0 is the educational tool for autism in primary school because it helps to stimulate, supports, develop skills and consolidate learning. This educational tool emphasizes on interactive online learning which can boost skill of student with special needs. Computer technology works well with special education children. Studies demonstrate that autistic children exhibit less disruptive or stim behaviours when using computers, and they experience increases in attending, response time, and problem solving. Therefore, library and school now, need to equip with suitable learning online that can be used by ASD users. This educational tool is created to provide a safe context for children with ASD to practice and improve their social skills and interactions. The mission of the educational tool is to positively impact the responsible of library and school as information store by offering experiences and tools to increase socialization. Novelty and Uniqueness: This educational tool provides an engaging multimedia approach to building linguistic skills which are often difficult for children with autism to acquire.